Let's solve the equation step-by-step, filling in the missing terms and descriptions as we go along:
-
Start with the original equation: \[ -9(-8q - 7) - 7q = 9q + 7 \]
-
Apply the distributive property: \[ -9 \cdot -8q - 9 \cdot -7 - 7q = 9q + 7 \] This simplifies to: \[ 72q + 63 - 7q = 9q + 7 \]
-
Combine like terms on the left side: \[ (72q - 7q) + 63 = 9q + 7 \] Which simplifies to: \[ 65q + 63 = 9q + 7 \]
-
Next, subtract \(9q\) from both sides: \[ 65q - 9q + 63 = 7 \] This simplifies to: \[ 56q + 63 = 7 \]
-
Now, subtract \(63\) from both sides: \[ 56q + 63 - 63 = 7 - 63 \] This simplifies to: \[ 56q = -56 \]
-
Finally, divide both sides by \(56\): \[ q = \frac{-56}{56} \] So: \[ q = -1 \]
Summary of Steps and Missing Descriptions:
- Apply the distributive property
- Combine like terms
- Subtract \(9q\) from both sides
- Subtract \(63\) from both sides
- Divide both sides by \(56\)
The complete solution is \(q = -1\).